3D printing of a thermo- and solvatochromic composite material based on a Cu(II)–thymine coordination polymer with moisture sensing capabilities - Maldonado, Noelia (2021)
This work presents the fabrication of 3D-printed composite objects based on copper(II) 1D coordination polymer (CP1) decorated with thymine along its chains with potential utility as an environmental humidity sensor and as a water sensor in organic solvents. This new composite object has a remarkable sensitivity, ranging from 0.3% to 4% of water in organic solvents. The sensing capacity is related to the structural transformation due to the loss of water molecules that CP1 undergoes with temperature or by solvent molecules' competition, which induces significant change in color simultaneously. The CP1 and 3D printed materials are stable in air over 1 year and also at biological pHs (5–7), therefore suggesting potential applications as robust colorimetric sensors. These results open the door to generate a family of new 3D printed materials based on the integration of multifunctional coordination polymers with organic polymers.